Pembuatan Pupuk Organik dari Limbah Rumah Tangga Sebagai Kegiatan Selama Masa Pandemi dan Poster Pencegahan Covid-19 di Kabupaten Wajo - Andi Tenri Ola (Universitas Hasanuddin, 2021)
Since the Covid-19 outbreak, there have been more activities will be done in the house. Starting from work, to daily activities such as sports and school are now carried out at home. In fact, not a few of them fill their spare time with new hobbies. One of the new hobbies that were popular during the Corona pandemic was farming. In planting, of course, you must pay attention to the planting medium or place where plants are grown. A good planting medium is to provide a dose of organic fertilizer in the medium. Making organic fertilizers by utilizing household waste can help recycle organic waste. Through this work program, the community is given education about making organic fertilizers from household waste. The aim of this activity is to increase public knowledge about making fertilizers as well as knowledge about healthy foods that must be consumed during the Covid-19 pandemic. This service method is by sharing videos and posters via social media. The 105th Thematic Real Work Lecture at Unhas